Optimalisasi Kepemimpinan Kepala Sekolah dalam Implementasi Deep Learning di SDN Candipari - Kurniawan, Satunggale; Putri, Falachaini Anitya; Jannah, Nur; Rahman, Muhammad Afifi (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2026)
This study aims to analyze the optimization of principal leadership in theimplementation of deep learning at Candipari Elementary School, Porong,Sidoarjo Regency. The research background is based on the importance ofadaptive and visionary leadership in supporting the integration of artificialintelligence-based learning technology in elementary schools. The study used adescriptive qualitative approach with data collection techniques through in-depthinterviews, participant observation, and documentation. Research informantsincluded the principal, teachers, and students involved in deep learning-basedlearning. Data analysis was conducted using a triangulation model of datareduction, data presentation, and conclusion drawing. The results show that theprincipal implemented transformational and collaborative leadership thatfocused on developing a digital-based vision, technology literacy training forteachers, and providing supporting infrastructure. The implementation of deeplearning increased interactivity, personalized learning, and enabled moreeffective monitoring of student learning progress. Despite constraints on initialteacher competencies and limited infrastructure, the principal's supportaccelerated adaptation and increased teacher and student motivation. Thus,optimizing principal leadership is a key factor in the successful integration ofdeep learning to improve the quality of learning in elementary schools.